AI AND GRIT TO IMPROVE PRINCIPALS' MANAGERIAL COMPETENCY USING THE ADDIE-SDGS MODEL - Iwan Sunarya Iqnasus Panjaitan; Nathanael Sitanggang; Irsan; Kisno; Sherly (RADJA PUBLIKA, 2025)
Introduction: School performance and instructional quality are directly impacted by the managerial competencies that principals must develop through effective training. In today's changing educational environment, strengths-based and resilience-building techniques are crucial, but they are frequently not integrated into traditional training paradigms. Together with Appreciative Inquiry (AI) and Grit, the ADDIE framework provides a thorough method for creating durable leadership skills that are in line with the objectives of global development. Objective: Using the ADDIE framework in conjunction with Appreciative Inquiry and Grit, this study attempts to create a training management model for school principals that is focused on the Sustainable Development Goals (SDGs) in order to enhance their managerial skills. Methods: Expert interviews, focus groups, and observations were used to gather qualitative data using a mixed-methods methodology in the context of research and development (R&D). N-Gain Score computations, paired-sample t-tests, and validity testing were used to assess quantitative data. The participants were purposefully chosen high school principals from the North Sumatra Region I Education Office. Results: With an Aiken's V of 0.90, the created SDGs training management model showed high validity. With an N-Gain Score of 0.73, which is considered strong, the model clearly enhanced managerial competencies. While the Grit component improved resilience and tenacity in handling managerial obstacles, the Appreciative Inquiry component promoted strengths-based leadership. Results indicate that combining ADDIE with AI and Grit results in a versatile and successful training approach that fosters long-term leadership growth. By focusing on resilience and positive capabilities, this method differs from traditional problem-focused training and meets the demands of modern educational leadership. The model's versatility and potential for digitization further increase its suitability for use in a range of educational settings. Conclusions: An inventive SDGs-focused training management strategy for school principals that incorporates ADDIE, Appreciative Inquiry, and Grit was successfully created and validated by the study. By encouraging strengths and resilience, this model successfully improves managerial competences and provides insightful advice for legislators and educational institutions looking to improve principal leadership.